Impact of strained channel on electrical properties of Junctionless Double Gate MOSFET - Kaharudin K.E.; Salehuddin F.; Zain A.S.M.; Roslan A.F.; Ahmad I. (Institute of Physics Publishing, 2023)
Band structure; Capacitance; Drain current; Electric field effects; Metals; MOS devices; Oxide semiconductors; Transconductance; Comparative analysis; Comprehensive analysis; Double gate MOSFET; Dynamic power dissipation; Intrinsic gate capacitance; Intrinsic gate delay; Strained channels; Transconductance generation factors; Power MOSFET